In Situ Assembly of 2D Conductive Vanadium Disulfide with Graphene as a High‐Sulfur‐Loading Host for Lithium–Sulfur Batteries. Issue 20 (19th April 2018) - Zhu, Xingyu; Zhao, Wen; Song, Yingze; Li, Qiucheng; Ding, Feng; Sun, Jingyu; Zhang, Li; Liu, Zhongfan
Abstract: Lithium–sulfur (Li–S) batteries are deemed to be one of the most promising energy storage technologies because of their high energy density, low cost, and environmental benignancy. However, existing drawbacks including the shuttling of intermediate polysulfides, the insulating nature of sulfur, and the considerable volume change of sulfur cathode would otherwise result in the capacity fading and unstable cycling. To overcome these challenges, herein an in situ assembly route is presented to fabricate VS2 /reduced graphene oxide nanosheets (G–VS2 ) as a sulfur host. Benefiting from the 2D conductive and polar VS2 interlayered within a graphene framework, the obtained G–VS2 hybrids can effectively suppress the polysulfide shuttling, facilitate the charge transport, and cushion the volume expansion throughout the synergistic effect of structural confinement and chemical anchoring. With these advantageous features, the obtained sulfur cathode (G–VS2 /S) can deliver an outstanding rate capability (≈950 and 800 mAh g −1 at 1 and 2 C, respectively) and an impressive cycling stability at high rates (retaining ≈532 mAh g −1 after 300 cycles at 5 C). More significantly, it enables superior cycling performance of high‐sulfur‐loading cathodes (achieving an areal capacity of 5.1 mAh cm −2 at 0.2 C with a sulfur loading of 5 mg cm −2 ) even at high current densities. Abstract : A novel VS2 –graphene hybrid fabricated via an in situ assembly route is employed as an efficient sulfur host material. The corresponding electrode can deliver an outstanding rate capability and impressive cycling stability. More importantly, it enables a high areal capacity with respect to the high‐sulfur‐loading cathodes even at high current densities.